Who was Abraham Lincoln? - Pascal, Janet B.; O'Brien, John, 1953- (New York : Grosset & Dunlap, 2008)
Looks at the life of Abraham Lincoln, a farmer boy who grew up to become the sixteenth president of the United States and the man responsible for leading the country through the Civil War.
Who was Abraham Lincoln -- Life in a log cabin -- The wider world -- A member of Congress -- The great debater -- Mr. President -- Civil War -- The end of slavery -- A two-minute speech -- The war is won -- Farewell to the president.
Includes bibliographical references (p. 104).
5.2
3-6
720L
T
Keywords: Lincoln, Abraham, -- 1809-1865 -- Juvenile literature; Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865.; Presidents -- United States -- Biography -- Juvenile literature; Presidents; Presidents -- United States -- Biography; Biographies